Ammonia volatilization from enhanced-efficiency urea on no-till maize in brazilian cerrado with improved soil fertility - Cancellier,Eduardo Lopes (2016)
ABSTRACT High nitrogen losses by ammonia volatilization are expected when urea is used as the source of N. The use of controlled-release urea and urease inhibitors are possible strategies to reduce such losses and increase nitrogen use efficiency. This study aimed to evaluate nitrogen losses by ammonia volatilization from stabilized, slow and controlled release urea and its absorption by maize grown under no-till in an improved Cerrado soil. Four N sources were used: conventional urea, urea + N-(n-butyl) thiophosphoric triamide (NBPT), urea + Cu and B and urea coated by sulfur + polymers. These N sources were surface applied along the rows using three N doses of 100, 150 and 200 kg ha-1. No N was added to the control. Data were collected regarding N losses by volatilization, the N contents accumulated in the stubble and grains, and the yields of the stubble and grains. Stabilized urea and slow release urea were efficient for postponing the ammonia volatilization peaks. The urease inhibitors postponed the peaks for up to two days, reducing the accumulated volatilization by 18% when compared with common urea. Polymer sulfur coated urea resulted in a 37% reduction in ammonia volatilization. Increasing the N application rate to 200 kg ha-1 resulted in 16% greater yields and 37% greater N accumulation in the plants relative to the control. However, the stabilized and slow-release urea did not improve the N accumulation or yield. Consequently, the nitrogen use efficiency of maize was not improved relative to the use of conventional urea.